Regionalism Approach on Management of Refugee to Protect Refugee Rights: Lesson learned from Africa and Asia Regions - Kusumo, Ayub Torry Satriyo (Faculty of Law, Universitas Jambi, 2023)
This study aims to explore the experience of managing refugees in other regions, such as Africa and Asia as well as the protection of their rights. This study focused on regions with developing countries but was not limited to. This study, which was qualitative in nature, looked at a variety of texts, including both scientific and grey-literature sources, and other periodicals. The literature was chosen based on relevance and had its information critically evaluated. The gathered data was systematically and legally examined. The 1951 Geneva Convention and the 1967 Protocol, as well as other international law sources pertaining to refugees, serve as the main legal sources in this study. Analytical thinking will be used to gather and analyze the data. Learning from more developed countries is also one of the efforts that are worth the try to build comprehensive cooperation. However, the unique characteristics of each region need to be taken into account for building a suitable model for managing refugees. Close coordination and cooperation with international bodies concerning refugees are also needed since countries have limited resources.